Perspectivas de uso de métodos de avaliação por usabilidade e UX no domínio da AR Sandbox - Darley, Natália Toralles (2021)
The way in which the user interacts with the digital world is becoming increasingly natural and immersive, such as Tangible User Interfaces, which allow users to manipulate digital elements through body gestures. Such interaction form addresses new requirements to be raised when it is intended to develop interfaces of this type. Physical elements of interaction, space of use and collaborative activities are characteristics that Tangible Interfaces differ from common interfaces, such as graphical ones. However, there are no adequate evaluation methods for evaluating tangible interfaces and considering their characteristics. This work proposes to show that the evaluation methodologies of known interfaces are not suitable to be applied to the Tangible User Interfaces, for this purpose a survey of the evaluation methodologies of Usability and User Experience (UX) through the investigation of requirements of reviews of AR Sandbox, an application for learning topography on a tangible map.